MODEL KINETIKA REAKSI PEMBENTUKAN POLYOL BERBASIS MINYAK SAWIT - La Ifa; Sumarno Sumarno; Susianto Susianto; Mahfud Mahfud (Dept. of Chemical Engineering, Diponegoro University, 2012)
REACTION KINETIC MODEL OF RBD PALM OIL BASED-POLYOL PRODUCTION. Polyol, a raw material of polyurethane, has successfully been produced from a renewable resource namely RBD palm oil. This polyol was made by firstly adding a peroxyacetic acid formed in situ from H2O2 and CH3COOH with H2SO4 as cataliyst into RBD palm oil to form epoxidized RBD palm oil. The epoxidized palm oil then was added to a mixture of methanol (MeOH), isopropanol (IPA), and H2SO4 for 2 hours at 60oC so that palm oil-based polyol was formed. The main equipment used in this research was a 500 mL three necked flask, equipped with a reflux condeser, thermometer, water bath and magnetic stirrer. The product was analysed using a titration method and Infra Red (IR) Spectroscopy. It was obtained that the produced palm oil-based polyol has a value of hydroxyl number of 150-209 mg KOH/g sample and a viscosity of 740.777 cP. These results are in accordance with other polyol products from other sources. The kinetic of palm oil-based kinetic was studied and the best model of the reaction rate equation was where k’ = 3.399 e-2391.,6/RT. The unit of k is L2 mol-2 menit-1 . The average error of the equation is 4,549%. Polyol, bahan baku polyuretan, telah berhasil dibuat dari bahan baku terbarukan yakni polyol berbasis RBD palm olein. Polyol ini mula-mula dibuat dengan menambahkan asam peroksi asetat yang dibentuk secara in situ dari H2O2 dan CH3COOH dengan katalis H2SO4 kedalam RBD palm olein untuk membentuk RBD palm olein terepoksidasi. RBD palm oil terepoksidasi ditambahkan kedalam campuran metanol (MeOH), isopropanol (IPA) dan sejumlah katalis H2SO4 selama 2 jam pada suhu 60 oC sehingga terbentuk polyol berbasis RBD palm oil. Peralatan utama yang digunakan dalam percobaan pembuatan polyol adalah labu leher tiga 500 mL dilengakapi dengan kondesor reflux, termometer, water bath dan magnetic stirrer. Polyol produk dianalisa bilangan hidroksil dengan cara titrasi dan dianalisis dengan Infra Red (IR) Spectroscopy. Polyol berbasis RBD palm oil yang dihasilkan memiliki bilangan hidroksil 150-209 mg KOH/g sampel dan viskositas 740,777 cP. hasil ini sebanding dengan polyol yang dihasilkan dari sumber minyak yang lain. Kinetika reaksi polyol berbasis RBD palm oil telah dipelajari dan hasil terbaik didekati dengan persamaan laju reaksi yang diperoleh pada penelitian adalah dimana k’ = 3,399 e-23913,6/RT dalam satuan L2 mol-2 menit-1. Kesalahan estimasi rata-rata adalah 4,549%. Kata kunci: model kinetika; RBD palm oil; polyol